Scoliosis severity does not impact the risk of scoliosis in family members. Issue 2 (March 2018) - Rudnick, Samuel B.; Zabriskie, Hannah; Ho, Justin; Gurnett, Christina A.; Dobbs, Matthew B.
Abstract : Does scoliosis severity increase scoliosis risk or severity in relatives? In a cohort of 1257 severe idiopathic scoliosis patients, the percentage with at least one affected relative was compared across the categories of patient sex, major curve severity (Cobb angle), and treatment method. In total, 138 (11%) of 1257 patients had at least one affected first-degree relative and 59 (5%) had at least one affected second-degree relative. As expected, males were more likely to have affected first-degree relatives than females (18 vs. 10% with a risk difference of −0.0864) [95% confidence interval (CI): −0.14 to −0.03; P =0.0002]. However, the major curve severity of the patient (<25°, 25°–49°, and ≥50°) did not impact the prevalence of having at least one affected relative ( P =0.69). Surgically treated patients had no greater risk than nonsurgically treated patients of having either an affected relative or a surgically treated relative [11 vs. 11% (odds ratio: 0.912; 95% CI: 0.640−1.299, P =0.61), 6 vs. 5% (OR: 0.788; 95% CI: 0.485−1.280, P =0.34), respectively]. Therefore, our data suggest that scoliosis severity does not independently influence the risk of either scoliosis or its severity in family members.